Analysis of Papuan Students' Learning Motivation in Online Learning for Elementary Science Physics Courses - Reza Mareta Putri; Ali Mustadi; Kintan Limiansih (AL-ISHLAH: Jurnal Pendidikan, 2022)
One of the policies made by the government to break the chain of spread of the Covid-19 virus is in the education sector, namely changing the face-to-face learning system into online learning. However, in online learning itself, not all students are successful in its application, there are many obstacles and obstacles they experience. The purpose of this study was to analyze the learning motivation of Papuan students in online learning. The method used in this research is descriptive with a qualitative approach. The results of this study say that Papuan students' learning motivation in online learning can be said to be good even though there are several obstacles related to online learning techniques. The results of the study were seen based on indicators of learning motivation, namely, the desire to succeed, the encouragement and curiosity, the increasing activities in learning, the existence of a conducive learning environment, the appreciation in learning.